2005
DOI: 10.1038/sj.ijo.0802895
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium and dairy foods in high protein, energy-restricted diets on weight loss and metabolic parameters in overweight adults

Abstract: OBJECTIVE:To compare the effects two high-protein (HP) diets that differ in dietary calcium and protein source on weight loss, body composition, glucose and lipid metabolism, markers of liver function, fibrinolysis and endothelial function and blood pressure. DESIGN: Randomized, parallel study (12 wk of energy restriction, 4 wk of energy balance) of high dairy protein/high-calcium (DP, 2400 mg Ca/d) and high mixed protein/moderate calcium (MP, 500 mg Ca/d) diets (5.5 MJ/d, 34% protein, 41% carbohydrate, 24% fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
2
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 38 publications
4
115
2
7
Order By: Relevance
“…Besides restriction of energy intake to a fixed value, these two studies had some other distinct features. The study by Bowen et al 33 compared a high-dairy diet with a high-protein diet, whereas those we included in the meta-analysis used a high-dairy diet versus diets with the same amount of protein. Another RCT done by Zemel et al 41 was a two-phase RCT that had 3 months of energy restriction to 1200--1500 kcal per day and a 6-month maintenance phase.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Besides restriction of energy intake to a fixed value, these two studies had some other distinct features. The study by Bowen et al 33 compared a high-dairy diet with a high-protein diet, whereas those we included in the meta-analysis used a high-dairy diet versus diets with the same amount of protein. Another RCT done by Zemel et al 41 was a two-phase RCT that had 3 months of energy restriction to 1200--1500 kcal per day and a 6-month maintenance phase.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…We found that two papers, 33,41 which administered energy restriction, had confined the energy intake into a defined certain value in both intervention and control groups, whereas other studies restricted the energy intake of participants to the amount of 500 kcal less than their computed daily energy requirement. Because restriction of energy to fixed values can directly affect weight change, 33,41 we preferred not to include the results of these two studies in the systematic review and meta-analysis; however, findings from the maintenance phase of study done by Zemel et al 41 were included in our systematic review. Besides restriction of energy intake to a fixed value, these two studies had some other distinct features.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…Total RNA (1 μg) was reverse-transcribed using Superscript II Reverse Transcriptase (Invitrogen, Carlsbad, CA, USA) with oligo-d(T) [12][13][14][15][16][17][18] as primer. After reverse transcription, the same batch of diluted cDNA was subjected to real-time polymerase chain reaction (PCR) to amplify target genes.…”
Section: Glp-1 Release Studymentioning
confidence: 99%
“…As regulators of protein metabolism, branched-chain amino acids (BCAAs; leucine, isoleucine, and valine) have also been reported to improve glucose and cholesterol metabolism [13,14] and control appetite [15]. A study by Bowen et al [16] suggested that the protein component of dairy appears to be more important for weight loss than calcium in over-weight adults. Therefore, likely candidates for these additional effects of dairy are casein and whey and its high concentrations of BCAAs.…”
Section: Introductionmentioning
confidence: 99%
“…Seven published weight‐loss studies from our research group,19, 20, 21, 22, 23, 24, 25 which had a total body dual‐energy x‐ray absorptiometry scan at baseline and 12 weeks and had a minimum of measures of glucose and lipids at each time point, were combined electronically for analysis. All studies followed a similar protocol, with variations in the amount of protein, carbohydrate, and fat, and had similar amounts of weight loss.…”
Section: Methodsmentioning
confidence: 99%